La cohabitation religieuse dans les villes Européennes, Xe - XVe siècles Religious cohabitation in European towns (10th-15th centuries) - Tolan, John; Boissellier, Stéphanie (Religion and Law in Medieval Christian and Muslim Societies, 2014)
Medieval towns, from Portugal to Hungary to Egypt, were places of contact between members of different religious communities, Muslim, Christian and Jewish, who rubbed shoulders in the ports and on the streets, who haggled in the markets, signed contracts, and shared wells, courtyards, dining tables, bath houses, and sometimes beds. These interactions caused legal problems from the point of view of the Jewish, Christian and Muslim judicial scholars of the middle ages, not to mention for the rulers of these towns. These legal attempts to define and solve the problems posed by interreligious relations are the subject of this volume, which brings together the work of seventeen scholars from nine countries (France, Italy, Spain, Hungary, Portugal, Lebanon, Israel, Tunisia, USA), specialists in history, law, archeology and religion.